2021
DOI: 10.1097/brs.0000000000003960
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection Following Primary Definitive Fusion for Pediatric Spinal Deformity

Abstract: on behalf of the Japan Spinal Deformity Institute Study Group Study Design. A retrospective multicenter study. Objective. To determine the surgical site infection (SSI) rate, associated risk factors, and causative pathogens in pediatric patients with spinal deformity. Summary of Background Data.There have been no extensive investigations of the risk factors for SSI in Japan. Methods. Demographic data, radiographic findings, and the incidence of SSI were retrospectively analyzed in 1449 pediatric patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 34 publications
(82 reference statements)
1
17
0
Order By: Relevance
“…This multicenter study examined the association between ARBT and postoperative infections in children treated with spinal fusion. The observed frequencies of transfusion and postoperative infection align with published findings in this patient population 34-36,52-54 . Our analysis was also consistent with prior studies in identifying several risk factors for postoperative infection, including age, sex, ASA status, neuromuscular spinal deformity, operative time, number of spinal levels fused, and ARBT 36,55 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This multicenter study examined the association between ARBT and postoperative infections in children treated with spinal fusion. The observed frequencies of transfusion and postoperative infection align with published findings in this patient population 34-36,52-54 . Our analysis was also consistent with prior studies in identifying several risk factors for postoperative infection, including age, sex, ASA status, neuromuscular spinal deformity, operative time, number of spinal levels fused, and ARBT 36,55 .…”
Section: Discussionsupporting
confidence: 89%
“…The rate of allogeneic blood transfusion ranges from 17.8% for idiopathic scoliosis to 57% for neuromuscular scoliosis 34 , 35 . Observational studies examining the association between ARBT and postoperative infections in this population have shown conflicting results 36 - 38 . Inconsistent findings may have resulted from methodologic limitations, such as small sample size and inadequate bias control 37 , 39 .…”
mentioning
confidence: 99%
“…A modification to include patients who are incontinent or at an increased risk of SSI allowed this to reach consensus (Tables 3 and 4). Notably, data supporting the use of preoperative urine cultures is only present in myelomeningocele patients, to our knowledge 5. Preoperative nutritional assessment was also a BPG in 2013 but only reached consensus when using BMI percentile for age in the current BPG 24.…”
Section: Discussionmentioning
confidence: 91%
“…48 Only, 1 study reported that BMI was not independently associated with infection risk among AIS patients. 51 8,18,19 Idiopathic, NMS, syndromic, congenital Pulmonary comorbidities 20,21 NMS GERD 22 NMS Preoperative WBC count 23 NMS Preoperative urine cultures 24 NMS Postoperative weight gain/loss 20 NMS Preoperative lumbar kyphosis 25 NMS Lenke curve classification 26 AIS Rod construct type 27,28 EOS, NMS Operative duration 29 Idiopathic, NMS, syndromic, congenital 2 Prevention Insufficient Preoperative Staphylococcus aureus nasal swabs and subsequent decolonization 30 AIS Preoperative MRSA screening and modification of antibiotic regimen 31 Idiopathic, NMS, syndromic, congenital Intraoperative redosing of IV antibiotics 32 Idiopathic, NMS, syndromic, congenital Type of cephalosporin for intraoperative administration 33 AIS Povidone-iodine irrigation alone (without intrawound vancomycin powder) 34 AIS Continued postoperative antibiotic prophylaxis 35,36 Idiopathic, NMS, syndromic, congenital Prophylactic hyperbaric oxygen therapy 37 NMS Plastic multilayered closure 38 or offset layered closure 39 EOS, NMS, syndromic, congenital Conclusions: There is grade B evidence that increased BMI is associated with greater risk of SSI after scoliosis surgery in pediatric populations.…”
Section: Risk Factorsmentioning
confidence: 99%
“…One Level III study reported that American Society of Anesthesiologists (ASA) class 3 patients had greater odds of acute postoperative infection than ASA class 2 patients, 35 while 2 Level III studies reported that ASA class was not a significant predictor of SSI occurrence. 29,59 Conclusions: There is grade C conflicting evidence that ASA class is associated with SSI risk after scoliosis surgery in pediatric populations.…”
Section: Higher American Society Of Anesthesiologists Classmentioning
confidence: 99%